The association between family dysfunction and admission to an acute mental health inpatient unit: a prospective study. (12th December 2022) - Tan, J. H. P.; Conlon, C.; Tsamparli, A.; O'Neill, D.; Adamis, D.
Abstract : Objectives: With the shift from deinstitutionalization to community care in mental health services, relatives of persons with severe and enduring mental illnesses have had to take over the role as primary caregivers. Disturbed family dynamics have been observed within families with an 'ill' member. Although schizophrenia and related mental illnesses are biologically based disorders, environmental stress (including stress within family relationships) plays a major role in the onset and maintenance of symptoms. With this study, we assume that family dynamics play a central role in the course of severe psychiatric illness and hypothesized that dysfunction within family systems is a prognostic indicator of hospitalization in the course of schizophrenia/bipolar and schizoaffective disorders. Methods: Prospective, observational cohort study evaluating family functioning of 121 patients (schizophrenia/bipolar and schizoaffective disorder) from community at baseline and followed-up over 12-month period after recruitment. Measurements included demographics, diagnosis, Family Assessment Device – General Functioning, Perceived Criticism Scale, Brief Psychiatric Rating Scale, Global Assessment of Functioning and Social Support Questionnaire-6. Results: Significant differences found between patients admitted and not admitted during the 12-month time period for age ( p = 0.003), Brief Psychiatric Rating Scale (BPRS; p = 0.026), Family Assessment Device – General Functioning (FAD-GF; p = 0.007) and Social Support Questionnaire total satisfaction level ( p = 0.042) at baseline. Bivariate analysis showed that those admitted into hospital were younger with a higher BPRS score, less social satisfaction and disturbed family dynamics. FAD-GF ( p = 0.006) and age ( p = 0.022) were significant independent predictors for admission. Conclusion: This provides further evidence supporting importance of promoting better family functioning through modified family dynamics, integrating and involving family into the care of such patients.